HATHERSAGE NUMERICAL IDENTITY LAB: MARSDEN, THE NEW FREEWOMAN, AND THE EGOIST AGAIN - Terence Rajivan Edward, (IJRDO - Journal of Social Science and Humanities Research, 2022)
In this paper, I respond to Scholes’s question of whether The Freewoman, The New Freewoman, and The Egoist, all of which were edited by Dora Marsden, were one journal or three.